ALASAN MENOLAK LAMARAN : KAJIAN HISTORISISME TERHADAP CERITA RAKYAT “PUTRI TUJUH” - Susanti, Triana; Suri, Dian Ratna; Widyastuti, Sri Harti; Wiyatmi, Wiyatmi (Fakultas Bahasa dan Sastra Indonesia Universitas Jenderal Soedirman, 2025)
Folklore is a form of literature that lives orally, namely literature that is spread in unwritten form, transmitted orally from generation to generation. The research aims to look further at how past societies formed and conveyed social values ​​through folklore, especially in the folklore of Putri Seven. This folklore is analyzed using a historicism approach. In this research, we provide an overview of the traditional traditions that regulate the order of marriage and the importance of the role of parents in determining their child's mate, both male and female, illustrating how strong the relationship between customs is in the life of Malay society, as well as understanding the reasons for Ratu Cik Sima's proposal to the Prince. Empang Kuala for his youngest daughter, Putri Mayang Sari. The story of Putri Tujuh describes the conflict resulting from traditional marriage rules, namely approval of the proposal because it is traditional for the eldest daughter to get married first. This shows the important impact of tradition in influencing social practices and maintaining cultural identity. With the study of historicism in folklore, it makes a new contribution to literature. Keyword: historicism, putri tujuh, folklore, Riau malay culture